2017
DOI: 10.1002/rth2.12008
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐minimization analysis of venous thromboembolism diagnosis: Comparison of standalone imaging with a strategy incorporating D‐dimer for exclusion of venous thromboembolism

Abstract: Summary Essentials A venous thromboembolism (VTE) diagnostic strategy is economical compared to imaging alone.Applied a VTE diagnostic strategy to a D‐dimer multicenter study for cost‐minimization analysis.Average diagnostic test costs for patients were significantly lower with a diagnostic strategy.Implementation of a VTE diagnostic strategy reduces the diagnostic costs for a hospital. BackgroundThe burden of healthcare costs has substantially risen in the last few decades. One possible contributing factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Cost reduction would have been even higher in other countries like the United States with calculations made from local estimates. 45 In that connection, Blondon et al evaluated the cost effectiveness of such a strategy by using a decision tree aimed at simulating the diagnosis strategy of PE and relevant present and future outcomes in a cohort of patients with a non-high PTP of PE with a life-term horizon and a health-care system perspective. They concluded that the use of an age-adjusted cut-off resulted in a clinically non-significant decrease in quality-adjusted life-years (QALY) but important cost reductions of above $80 million per year for the US health-care system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cost reduction would have been even higher in other countries like the United States with calculations made from local estimates. 45 In that connection, Blondon et al evaluated the cost effectiveness of such a strategy by using a decision tree aimed at simulating the diagnosis strategy of PE and relevant present and future outcomes in a cohort of patients with a non-high PTP of PE with a life-term horizon and a health-care system perspective. They concluded that the use of an age-adjusted cut-off resulted in a clinically non-significant decrease in quality-adjusted life-years (QALY) but important cost reductions of above $80 million per year for the US health-care system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on the reimbursement costs of D‐dimer, CTPA, and CUS in France, this strategy was found to be cost effective in the validation cohort, with a 6.9% reduction in diagnostic costs for PE and a 5.1% reduction in diagnostic costs for DVT, compared to the conventional strategy. Cost reduction would have been even higher in other countries like the United States with calculations made from local estimates 45 . In that connection, Blondon et al evaluated the cost effectiveness of such a strategy by using a decision tree aimed at simulating the diagnosis strategy of PE and relevant present and future outcomes in a cohort of patients with a non‐high PTP of PE with a life‐term horizon and a health‐care system perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated cost reduction of successfully implementing a VTE diagnostic strategy involving initial clinical assessment versus imaging alone was found to be 38% for patients with suspected PE and 24% for suspected DVT. Assuming the proportion of suspected PE and DVT patients to be 30% and 70%, respectively, the weighted average cost reduction per suspected VTE patient was 32% [6].…”
Section: Introductionmentioning
confidence: 99%
“…A cost-effectiveness analysis on multiple different diagnostic strategies in a hospital has been previously performed [ 18 , 19 ]. Verma et al conducted a cost-minimization analysis and found that incorporating a D-dimer assessment into the diagnostic protocol in hospital setting instead of referring every DVT patient to US saved 24% of costs [ 20 ]. We are not aware of any studies which have estimated the overall costs of the LCUS protocol.…”
Section: Introductionmentioning
confidence: 99%